Antioxidant activities and lutein content of 11 marigold cultivars (Tagetes spp.) grown in Thailand - Ingkasupart,Pajaree (2015)
Antioxidant activities and total phenolic content (TPC) were analyzed in ethanol extracts of 11 marigold cultivars grown in Thailand. Antioxidant activity assays performed in this study were the 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical cation scavenging activity, ferric ion reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, oxygen radical absorbance activity (ORAC), and superoxide anion radical scavenging activity (SRSA) assays. ‘Optiva Orange’ showed the best activity in the ORAC assay and in % SRSA, as well as the highest content of lutein (20.59 mg), gallic acid (25.77 mg), and quercetin (12.61 mg) per gram dry marigold petal among the 11 cultivars. Furthermore, ‘Optiva Orange’ showed the highest lutein yield per plant, as compared to other cultivars. In contrast, ‘Rodeo Gold’ showed the highest activity by ABTS testing (0.92 mmol of trolox/g dry sample), as well as an 89.90% inhibition of DPPH. Lutein content showed a positive correlation with TPC and all antioxidant activity assays. In conclusion, ‘Optiva Orange’ and ‘Rodeo Gold’ could be utilized as a good lutein source for functional food products and cosmetics.